2017
DOI: 10.1177/1525822x17729341
|View full text |Cite
|
Sign up to set email alerts
|

Interviewer–respondent Interactions in Conversational and Standardized Interviewing

Abstract: Standardized interviewing (SI) and conversational interviewing are two approaches to collect survey data that differ in how interviewers address respondent confusion. This article examines interviewer–respondent interactions that occur during these two techniques, focusing on requests for and provisions of clarification. The data derive from an experimental study in Germany, where the face-to-face interviews were audio-recorded. A sample of 111 interviews was coded in detail. We find that conversational interv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 12 publications
0
8
0
Order By: Relevance
“…In terms of interview duration, the CI technique resulted in interviews that were roughly 1 min longer, on average, but this difference was not significant. This may have been due to the fact that many questions did not end up requiring extensive clarification from the interviewers (Mittereder et al ., ). The CI technique did result in higher within‐interviewer variance in interview length, which was expected, and marginally higher between‐interviewer variance in duration of interview (which also was expected).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…In terms of interview duration, the CI technique resulted in interviews that were roughly 1 min longer, on average, but this difference was not significant. This may have been due to the fact that many questions did not end up requiring extensive clarification from the interviewers (Mittereder et al ., ). The CI technique did result in higher within‐interviewer variance in interview length, which was expected, and marginally higher between‐interviewer variance in duration of interview (which also was expected).…”
Section: Discussionmentioning
confidence: 97%
“…the interviewers became better at using their assigned technique) after receiving this feedback. Overall, when analysing a subsample of these recordings in detail for interviewers in each of the two groups, we found that the CI and SI techniques had been implemented correctly and consistently (Mittereder et al ., ).…”
Section: Experimental Designmentioning
confidence: 97%
See 1 more Smart Citation
“…We first examine interviewer effects across our 10 interviewers and afterward ask whether they help explain the mode effect on the volume of names. Studies suggest that interviewer effects result from differences among interviewers in building rapport, persuading respondents to answer sensitive questions (West and Blom 2017), probing for detail (Houtkoop-Steenstra 1996; Van der Zouwen and Van Tilburg 2001), and getting clarifications (Mittereder et al 2017). Other studies suggest that network differences arise if some interviewers learn to shorten interviews by eliciting fewer names (Harling et al 2018; Josten and Trappman 2016; Valente et al 2017).…”
Section: Interviewer Effectsmentioning
confidence: 99%
“…The popularity of interviews as a source of data about management and organizations has translated into a rich coverage of this method in methodological literature, including the work which address interviews with respect to reflexive interpretation (Alvesson, 2003(Alvesson, , 2011, sampling (Saunders & Townsend, 2016), data collection (Bourne & Jenkins, 2005), or managing the interview situation (Dundon & Ryan, 2010;Mittereder, Durow, West, Kreuter, & Conrad, 2017).…”
Section: Introductionmentioning
confidence: 99%